1982
DOI: 10.1038/sc.1982.64
|View full text |Cite|
|
Sign up to set email alerts
|

Post-traumatic syringomyelia

Abstract: Abstract. A description is given of the syndrome of post-traumatic syringomyelia amongst patients with traumatic spinal injuries seen at the National Spinal Injuries Centre. The diagnosis was made on clinical grounds. It was confirmed wherever possible by neuroradiology prior to surgery; one case was confirmed only at post mortem. The incidence of the condition was found to be in keeping with other large series but, in contrast, no difference was found between the time of onset after injury between complete an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

1983
1983
2013
2013

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 10 publications
1
25
1
Order By: Relevance
“…These two phenomena are increased when there is a blockage in the subarachnoid space. The signi®cant correlation with factors of venous hyperpressure found in this present study, the worsening reported in the literature after straining, 8,24 weightlifting exercises, 25 forced expiratory through a closed glottis, coughing or Vasalva manoeuver, 24 lithotripsy, 26 comfort this theory.…”
Section: Radiological Analysis Of the Lesion Sitesupporting
confidence: 85%
“…These two phenomena are increased when there is a blockage in the subarachnoid space. The signi®cant correlation with factors of venous hyperpressure found in this present study, the worsening reported in the literature after straining, 8,24 weightlifting exercises, 25 forced expiratory through a closed glottis, coughing or Vasalva manoeuver, 24 lithotripsy, 26 comfort this theory.…”
Section: Radiological Analysis Of the Lesion Sitesupporting
confidence: 85%
“…During the first few hours and days, neurological deterioration may result from edema and other secondary changes involving one or two spinal cord segments adjacent to the original site of trauma. After a period of neurological stability, late delayed complications, such as progressive post-traumatic cystic myelopathy (syringomyelia) [1][2][3] or progressive post-traumatic myelomalacic myelopathy, 4,5 may produce new ascending neurological symptoms months, years, or even decades after the original injury.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of this rather rare late complication of paraplegia is estimated in the literature to be about 1.3° 0' which is much higher than the incidence of primary syringomyelia: about 0.01 °0 (Barnett, 1966;Vernon, 1982). In a recent publication an even higher incidence was noted: 3.2%, but in the case of complete paraplegia the figures reached those noted in the literature of 1.4°0 (Rossier, 1985).…”
Section: Post-traumatic Syringomyelia: Generalitiesmentioning
confidence: 60%